Applying the ADA : designing for the 2010 Americans with disabilities act standards for accessible design in multiple building types - Rhoads, Marcela Abadi (Hoboken, New Jersey : John Wiley & Son, Inc., 2013)
By showing how the Americans with Disabilities Act Accessibility Guidelines (ADAAG) has been applied in various contexts and building types, this illustrated book helps readers quickly understand the requirements of the ADAAG. Building types covered include healthcare facilities, elementary schools, hospitality facilities, office buildings, college and university facilities, retail and mixed-use facilities, performing arts facilities, and senior living. The author will note both new construction and renovations. The author, an architect, consults regularly on accessibility issues for clients including design professionals, building owners, and facility managers. Photographs and easy-to-understand descriptions illustrate practical applications of the guidelines for multiple building types including healthcare facilities, elementary schools, hospitality facilities, office buildings, college and university facilities, retail and mixed-use facilities, performing arts facilities, and senior living.
Acknowledgements -- Introduction -- 1. General guidelines / Marcela Abadi Rhoads -- 2. Retail and mixed-use facilities / Marcela Abadi Rhoads -- 3. Primary education / Wally Tirado -- 4. Secondary and postsecondary education / Wally Tirado -- 5. Hospitality / Jeromy Murphy -- 6. Healthcare and senior living communities / Greg Hunteman -- 7. Amusement parks and play areas / Marcela Abadi Rhoads -- 8. Historic preservation and remodels / Marcela Abadi Rhoads -- 9. Residential projects / Jeromy Murphy -- 10. Universal design beyond the ADA / Marcela Abadi Rhoads -- Appendix A: Reference tables -- Appendix B: Resources -- Index.
Includes bibliographical references and index.
Keywords: BARRIER-FREE DESIGN -- UNITED STATES